RADICALISM PREVENTION MOVEMENT: RELIGIOUS MANIFESTATION OF SHOLAWAT COMMUNITIES IN THE MATARAMAN - Fuad, A. Jauhar (UIN Maulana Malik Ibrahim Malang, 2020)
Religious traditions become a form of community religiosity. One’s religious attitude can be manifested in religious forms and actions through religious rituals such as prayer, fasting, zakat, pilgrimage, and other rituals such as tahlil, istighasha, and salawat. Public openness to religious traditions will close the space for radicalization. The research method uses a qualitative approach with data collection techniques, Interviews, documentation and focus group discussion. The findings of this study: first, the salawat council becomes a forum for people who have a spirit of religiosity in carrying out religious traditions. The development of salawat assemblies in the Mataraman region is quite a lot, but there are salawat assemblies having affiliations with FPI and defend against HTI. Second, the salawat council's existence received a response from Gus (young Kyai) who then brought the salawat council as a counterweight to the previous assembly. Its presence becomes a choice for the people in neutralizing radical understanding. As the community's religious universe grows, it needs an assembly that can lead to Islam's concept wasathiyah. Tradisi keagamaan menjadi wujud dari religiusitas masayarakat. Sikap religiusitas seseorang dapat diwujudkan dalam bentuk dan tindakan keagamaan melalui ritual-ritual kegamaan seperti, salat, puasa, zakat, haji, dan ritual lain seperti tahlil, istighasha, dan salawat. Keterbukaan masyarakat pada tradisi agama akan menutup ruang gerak radikalisasi. Metode penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data, wawancara, dokumentasi dan FGD. Temuan penelitian ini: pertama, majelis salawat menjadi wadah bagi masyarakat yang mimiliki spirit religiusitas dalam menjalankan tradisi keagamaan. Perkembangan majelis salawat di wilayah Mataraman cukup banyak, akan tetapi ada majelis salawat yang memiliki afiliasi dengan FPI dan melakukan pembelaan terhadap HTI. Kedua, keberadaan majelis salawat tersebut mendapat respon dari Gus (kyai muda) yang kemudian memunculkan majelis salawat sebagai penyeimbang majelis sebelumnya. Kehadirannya menjadi pilihan bagi umat dalam menetralisir paham radikal. Seiring meningkatnya semangat keagamaan masyarakat, maka dibutuhkan majelis yang dapat mengarahkan pada konsep Islam wasatiyah.